Mechanical and Physical Properties of Recombinant Spider Silk Films Using Organic and Aqueous Solvents - Tucker, Chauncey L. (American Chemical Society, 2014)
[Image: see text] Spider silk has exceptional mechanical and biocompatibility properties. The goal of this study was optimization of the mechanical properties of synthetic spider silk thin films made from synthetic forms of MaSp1 and MaSp2, which compose the dragline silk of Nephila clavipes. We increased the mechanical stress of MaSp1 and 2 films solubilized in both HFIP and water by adding glutaraldehyde and then stretching them in an alcohol based stretch bath. This resulted in stresses as high as 206 MPa and elongations up to 35%, which is 4× higher than the as-poured controls. Films were analyzed using NMR, XRD, and Raman, which showed that the secondary structure after solubilization and film formation in as-poured films is mainly a helical conformation. After the post-pour stretch in a methanol/water bath, the MaSp proteins in both the HFIP and water-based films formed aligned β-sheets similar to those in spider silk fibers.